Non-genetic factors affecting the meat quality and flavor of Inner Mongolian lambs: A review - Yuning Liu; Runhang Li; Ying Ying; Yandong Zhang; Yiying Huang; Hongxin Wu; Kejian Lin (Frontiers in Veterinary Science, 2022)
The Inner Mongolia Autonomous Region ranks first among the five major pastoral areas in terms of lamb breeding of China. The Inner Mongolia Autonomous Region has a vast territory, with many famous grasslands and thousands of forage plants and multiple local high-quality lamb breeds. After hundreds of years of artificial breeding and improvement, Mongolian sheep have developed many varieties. Different diets, feeding and treatment methods have effects on the production performance, lipid deposition and flavor composition of mutton sheep. Therefore, understanding the relationship among Inner Mongolian lamb, meat quality, and flavor will improve the production of high-quality mutton. The regulation of meat quality and flavor will have a profound impact on the deep processing and income-generating capabilities of mutton. Non-genetic factors affect the quality and flavor of mutton, which are more intuitive than genetic factors. In this review, we cover the contributions made by scientists to explore and improve the quality and flavor of Inner Mongolia lambs through non-genetic means, compare the differences between grazing and drylot-feeding in detail, and summarize some feed additives. We hope that based on our review, we can provide some inspiration to improve the meat quality of Mongolian sheep.